Diagnostic Performance of In‐Procedure Angiography‐Derived Quantitative Flow Reserve Compared to Pressure‐Derived Fractional Flow Reserve: The FAVOR II Europe‐Japan Study. Issue 14 (17th July 2018) - Westra, Jelmer; Andersen, Birgitte Krogsgaard; Campo, Gianluca; Matsuo, Hitoshi; Koltowski, Lukasz; Eftekhari, Ashkan; Liu, Tommy; Di Serafino, Luigi; Di Girolamo, Domenico; Escaned, Javier; Nef, Holger; Naber, Christoph; et al.
Abstract : Background: Quantitative flow ratio (QFR) is a novel modality for physiological lesion assessment based on 3‐dimensional vessel reconstructions and contrast flow velocity estimates. We evaluated the value of online QFR during routine invasive coronary angiography for procedural feasibility, diagnostic performance, and agreement with pressure‐wire–derived fractional flow reserve (FFR) as a gold standard in an international multicenter study. Methods and Results: FAVOR II E‐J (Functional Assessment by Various Flow Reconstructions II Europe‐Japan) was a prospective, observational, investigator‐initiated study. Patients with stable angina pectoris were enrolled in 11 international centers. FFR and online QFR computation were performed in all eligible lesions. An independent core lab performed 2‐dimensional quantitative coronary angiography (2D‐QCA) analysis of all lesions assessed with QFR and FFR. The primary comparison was sensitivity and specificity of QFR compared with 2D‐QCA using FFR as a reference standard. A total of 329 patients were enrolled. Paired assessment of FFR, QFR, and 2D‐QCA was available for 317 lesions. Mean FFR, QFR, and percent diameter stenosis were 0.83±0.09, 0.82±10, and 45±10%, respectively. FFR was ≤0.80 in 104 (33%) lesions. Sensitivity and specificity by QFR was significantly higher than by 2D‐QCA (sensitivity, 86.5% (78.4–92.4) versus 44.2% (34.5–54.3); P <0.001; specificity, 86.9% (81.6–91.1) versus 76.5% (70.3–82.0); P =0.002). Area under the receiver curve was significantly higher for QFR compared with 2D‐QCA (area under the receiver curve, 0.92 [0.89–0.96] versus 0.64 [0.57–0.70]; P <0.001). Median time to QFR was significantly lower than median time to FFR (time to QFR, 5.0 minutes [interquartile range, –6.1] versus time to FFR, 7.0 minutes [interquartile range, 5.0–10.0]; P <0.001). Conclusions: Online computation of QFR in the catheterization laboratory is clinically feasible and is superior to angiographic assessment for evaluation of intermediary coronary artery stenosis using FFR as a reference standard. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02959814.